A control study on treatment for benzodiazepine dependence with trazodone - Hong-ju ZHANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2013)
Objective To determine the efficacy and safety of trazodone in the treatment of benzodiazepine dependence. Methods Forty insomnia patients who met the Classification and Diagnostic Criteria of Mental Disorders in China Third Edition (CCMD-3) of dependence syndrome due to benzodiazepine were involved in the study. Patients were randomly assigned to trazodone group and placebo group for 3 months. The efficacy were assessed by Withdrawal Symptoms Checklist, Hamilton Anxiety Rating Scale (HAMA) and polysomnography (PSG). Adverse events were assessed by Treatment Emergent Symptom Scale (TESS). Results The Withdrawal Symptoms Checklist of trazodone group was significantly lower after 7 d treatment than that of placebo group (P = 0.000), and HAMA score of the trazodone group was also significantly lower after 15 d treatment than that of placebo group (P = 0.000). There were no difference in Withdrawal Symptoms Checklist and HAMA of placebo group before and after treatment. Withdrawal Symptoms Checklist and HAMA of the trazodone group were decreased after treatment (P = 0.000). In comparison with placebo group, sleep parameters of the trazodone, including total sleep time (TST), sleep efficiency (SE), sleep latency (SL) and slow wave sleep (SWS) time presented improvement after 7 d treatment (P = 0.000, for all). After trazodone treatment, total sleep time, slow wave sleep time, sleep efficiency and sleep latency were improved (P = 0.000, for all). No obvious adverse reaction occurred. There were no significant differences in TESS scores between pre- and post-treatment in both groups (P > 0.05). Conclusion Trazodone is markedly effective and safe in the treatment for benzodiazepine dependence.